Combination of acne treatment in women with prevention of complications using standard schemes of systemic retinoids - S. S. Ledentsova; N. I. Gulyaev; A. V. Gordienko; N. P. Gavrilova; L. S. Oreshko; P. V. Seliverstov (Лечащий Врач)
Currently, the first-line drugs for acne treatment are systemic retinoids. This group of drugs has a pronounced hepatotoxic effect, which should be taken into account when using them in standard acne treatment schemes. The aim of the study was to study the effect of ursodeoxycholic acid on the tolerability and effectiveness of systemic isotretinoin therapy in patients with severe acne taking combined oral contraceptives.